The Effect of Technology-enhanced Classroom in Middle School Education - Eyyam, Ramadan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The education system in North Cyprus is changing continuously in an effort to bring standards up to par with developed nations. The new system designed in 2005 is still not used effectively in most of the schools in North Cyprus. Educational technology, viewed as an inseparable part of education, has also been introduced into the new North Cyprus education system although the implementation of technology has not occurred as planned. The present study’s objective, therefore, is to investigate how technology use affects student progress. For this purpose, in the present study the experiment was conducted in technology-enhanced classroom. Furthermore, the effect of technology-enhanced classroom was examined with respect to gender and the multiple intelligence (MI) profiles of students. A private school in the Famagusta district was chosen and the progress of all 82 seventh grade students (34 female and 48 male) was observed in two subjects, English and Mathematics. In each part of this experimental study, students were divided into treatment and control groups using the cross-implementation experimental method. The study lasted 40 contact hours for each subject. In treatment groups for both Mathematics and English, lessons were held in technologyenhanced classroom whereas in control groups no technology was implemented, in other words, traditional instruction was maintained. The results indicate that in English lessons, technology-enhanced classroom did not make a significant difference whereas it did seem to improve students’ performance in Mathematics lessons, even though the difference was not statistically significant. Also, no statistically significant differences were found with regard to the gender of students. On the other hand, when the MI profiles of students were taken into consideration, the results revealed that the kinesthetic, verbal, and logical intelligences of students were predictors of their success in Mathematics lessons in technology-enhanced classroom. The study also reveals that students had positive opinions on technology use as did English teachers whereas Mathematics teachers felt rather negative towards the implementation of technology. Although the literature indicates that technology use affects classroom instruction positively, some research has yielded similar results to those of the present study, where technology-enhanced classroom was found not to be effective. This suggests that the research should be repeated on a longitudinal basis in order to obtain more reliable results which could contribute to the education system in North Cyprus. Keywords: instructional technology, cross-implementation experimental method, English, Mathematics, opinions on technology use, secondary education, instructional design. ………………………………………………………………………………………………………………………… ÖZ: Kuzey Kıbrıs eğitim sistemi, gelişmiş ülkelerle aynı düzeye ulaşma çabası ile sürekli değişim içindedir. 2005 yılında düzenlenmiş olan yeni sistem, halen Kuzey Kıbrıs’taki okulların çoğunda etkili bir biçimde uygulanamamaktadır. Eğitimin ayrılmaz bir parçası olarak kabul edilen öğretim teknolojileri de Kuzey Kıbrıs’ın yeni eğitim sistemine dahil edilmiştir ancak teknolojinin uygulanması planlandığı gibi gerçekleşmemiştir. İşbu araştırmanın amacı teknolojinin öğrencilerin başarısını nasıl etkilediğini incelemektir. Bu nedenle bu çalışmadaki deney, teknoloji destekli sınıfta gerçekleştirilmiştir. Teknoloji destekli sınıfın olası etkisi, öğrencilerin cinsiyeti ve çoklu zeka profillerine bağlı olarak da incelenmiştir. Araştırma için Gazimağusa ilçesinde özel bir okul seçilmiş ve tüm yedinci sınıf öğrencilerinin (34 kız ve 48 erkek olmak üzere toplam 82) İngilizce ve matematik derslerindeki gelişimi izlenmiştir. Bu deney araştırmanın her iki bölümünde, öğrenciler, çapraz-uygulama deneysel yöntemi kapsamında deneysel ve kontrol olmak üzere iki gruba ayrılmıştır. Deney, her bir ders için 40 ders saati sürmüştür. Hem Matematik hem İngilizce derslerinde deney gruplarında teknoloji destekli sınıflarda eğitim verilirken, kontrol gruplarında herhangi bir teknoloji kullanılmamış, başka bir deyişle dersler geleneksel öğretim yöntemleriyle yürütülmüştür. Sonuçlar; teknoloji destekli sınıfın İngilizce dersinde önemli bir farka yol açmazken Matematik dersinde öğrencilerin başarısını olumlu yönde etkilediği, ancak farkın istatistiksel olarak anlamlı olmadığını göstermiştir. Öğrencilerin cinsiyeti açısından da istatistiksel olarak anlamlı farklar elde edilmemiştir. Diğer yandan, öğrencilerin çoklu zeka profilleri göz önüne alındığında, öğrencilerin kinestetik, sözel, ve mantıksal zekalarının, teknoloji destekli sınıfta matematik derslerindeki başarılarını öngörmeyi sağlayan birer etmen oldukları görülmüştür. Araştırmanın sonuçları ayrıca, öğrencilerin ve İngilizce öğretmenlerinin teknoloji kullanımı konusunda olumlu görüşleri olduğunu ortaya koyarken, matematik öğretmenlerinin teknoloji uygulamalarına karşı olumsuz görüşleri olduğunu göstermiştir. Bu alandaki yayınlar teknoloji kullanmının sınıf içi öğretimi üzerinde olumlu etkileri olduğunu gösterse de, birtakım araştırmalarda işbu araştırmanın sonuçlarına benzer biçimde, teknoloji destekli sınıfın etkili olmadığı yolunda sonuçlar elde edilmiştir. Bu durum, araştırmanın uzun vadeli bir biçimde tekrarlanarak Kuzey Kıbrıs eğitim sistemine katkıda bulunacak biçimde daha güvenilir sonuçlar elde edilmesi gerektiğine işaret etmektedir. Anahtar sözcükler: öğretim teknolojileri, çapraz-uygulama deneysel yöntemi, İngilizce, matematik, teknoloji kullanımı üzerine görüşler, orta öğretim, öğretme Tasarımı.
Doctor of Philosophy in Educational Sciences. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of Educational Sciences, 2014. Supervisor: Assoc. Prof. Dr. Hüseyin Yaratan.
Keywords: Educational Sciences; Educational Technology; Audio-visual education; Instructional Technology, Cross-Implementation Experimental Method, English, Mathematics, Opinions on Technology Use, Secondary Education, Instructional Design